2018
DOI: 10.5125/jkaoms.2018.44.4.159
|View full text |Cite
|
Sign up to set email alerts
|

A comparative study of immediate wound healing complications following cleft lip repair using either absorbable or non-absorbable skin sutures

Abstract: ObjectivesThe aim of the study was to compare wound healing complications following the use of either absorbable or non-absorbable sutures for skin closure in cleft lip repair.Materials and MethodsThis was a randomized controlled trial conducted at the Department of Oral and Maxillofacial Surgery, Lagos University Teaching Hospital, Idi Araba, Lagos State, Nigeria. Sixty subjects who required either primary or secondary cleft lip repair and satisfied all the inclusion criteria were recruited and randomized int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(19 citation statements)
references
References 38 publications
(76 reference statements)
0
19
0
Order By: Relevance
“…All studies had at least some concerns for risk of bias. Studies assessed absorbable versus nonabsorbable suture (Shinohara et al, 1996; Collin et al, 2009; Datarkar et al, 2014; Alawode et al, 2018), tissue glue versus suture (absorbable or permanent) (Spauwen et al, 2006; Knott et al, 2007; Halli et al, 2012), and steri-strips versus tissue glue (Wilson and Mercer, 2008). Few studies showed significant differences between groups, and many studies used different outcome measures.…”
Section: Resultsmentioning
confidence: 99%
“…All studies had at least some concerns for risk of bias. Studies assessed absorbable versus nonabsorbable suture (Shinohara et al, 1996; Collin et al, 2009; Datarkar et al, 2014; Alawode et al, 2018), tissue glue versus suture (absorbable or permanent) (Spauwen et al, 2006; Knott et al, 2007; Halli et al, 2012), and steri-strips versus tissue glue (Wilson and Mercer, 2008). Few studies showed significant differences between groups, and many studies used different outcome measures.…”
Section: Resultsmentioning
confidence: 99%
“…The Journal of Oral and Maxillofacial Surgery (JOMS)45678910111213 was one journal title selected from journals indexed by Scopus and SCIE that was correctly classified as an oral surgery title. (Tables 1, 3) The Journal of the Korean Association of Oral and Maxillofacial Surgeons (JKAOMS)14151617181920212223 was one journal title selected from the journals indexed by Scopus only and was correctly classified as an oral surgery title. (Table 1) One journal title that was selected from journals not indexed by Scopus or SCIE and classified as an oral surgery title was Maxillofacial Plastic and Reconstructive Surgery (MPRS)24252627282930313233.…”
Section: Methodsmentioning
confidence: 99%
“…Additional searches were also done. Finally, only 6 trials (Shinohara et al, 1996;Spauwen et al, 2006;Bhuiyan et al, 2010;Datarkar et al, 2014;Rao et al, 2016;Alawode et al, 2018) met all inclusion criteria, and they were selected for qualitative analysis. A total of 299 participants who underwent CLP repair were included in the outcome evaluations.…”
Section: Description Of Studiesmentioning
confidence: 99%